(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
أجريت الدراسة على سمك الكارب Cyprinus carpio في وحدة السن لتربية الأسماك ( 211 عينة ) ، و تم تحديد التعداد العام للجراثيم في واحد غرام من عضلات الأسماك و غلاصمها ، و نسبة عزل كل من الجراثيم الكولونية Coliform ، و الكولونية البرازية Faecalis Coliform ، و تعدادها كمؤشرات لتلوث الأسماك و مدى صلاحيتها للاستهلاك البشري مباشرة أو بعد حفظها بالتبريد العادي ( 0 , -4C°) حتى عشرة أيام ، و دراسة نسبة عزل السلمونيلا Salmonella . و قد أوضحت الدراسة ارتفاع التعداد العام للجراثيم عن الحد الطبيعي المقبول عالميا (105 - 108 بكتريا حية / غ من الأنسجة ) [ 1] ، و عن الحد المسموح به في المواصفات القياسية للمواد الغذائية السورية ( 106 بكتريا حية / غ من الأنسجة ) . بلغ التعداد العام للجراثيم عند الفحص المباشر للعينات في كل من العضلات و الغلاصم ( 108 / غ ) ، و ازداد في العينات المحفوظة بالتبريد العادي حتى وصل في اليوم العاشر إلى ( 1013 / غ ) ، كما كانت نسبة عزل الجراثيم الكولونية في العضلات (97.58 %± 1,5) و في الغلاصم (95.26 % ± 0.32 ) ، و الكولونية البرازية في العضلات (61.35 % ± 2.6 ) و في الغلاصم (69.56 % ± 2.1 ) ، كما عزلت السلمونيلا (Salmonella typhi , S. para typhi A ) من العضلات (50.72 % ± 3.4 ) و في الغلاصم (64.45 % ± 2.4 ) . وبينت النتائج وجود تلوث لمياه الأحواض فقمنا بدراستها في عدة أمكنة حتى المصدر ، و قد ظهر ارتفاع تعداد الكوليفورم ، و الكوليفورم البرازية و عزلت السلمونيلا أيضا ، إلا أن مياه المصدر كانت سليمة و قد عثر على أحد الأنابيب المغذية للأحواض مكسورا و مكشوفا قرب الطريق العام ، كما أظهرت الدراسة أيضا عدم فاعلية التبريد العادي في حفظ الأسماك . The Study has been performed on Cyprinus Carpio at ALSIN Unit for fish Culture (211 samples). The total number of bacteria has been determined in 1 gr. of fish muscles and gills, and isolation rate of Coliforms and Faecalis Coliforms and counting same as indicators of fish pollution and if is fit for human consumption either directly, or after keeping in refrigerator (0 , -4ºC ) up to ten days . Also determining isolation rate of Salmonella. The study has shown the increase of total number of bacteria over what is accepted internationally (105 - 108 Alive Bacteria /gr. of Tissues) [ 1 ] , and over the tolerated rate of the Syrian Foodstuff Standard (106 Alive Bacteria l / gr. of Tissues ) The general Number of Bacteria at direct examination in each of the muscles and gills amounted to ( 108 / gr.) and it increased in the samples kept in ordinary refrigeration till it reached on the 10th day ( 1013 / gr ) . Isolation rate of Coliforms in the muscles amounted to ( 97.58 % ±1.5 ) and in gills amounted to ( 95.26 % ± 0.32 ) . Faecalis Coliforms in the muscles amounted to ( 61.35 %± 2.6 ) and in the gills amounted to ( 69.56 % ± 2.1 ) , while isolation rate for Salmonella ( Salmonella Typhi, S. para Typhi A ) was in the muscles ( 50.72 % ± 3.4 ) and in the gills ( 64.45 % ± 2.4 ) . The results have indicated the contamination of Basins Water; therefore, we have examined them in various sites up to the resource. A rise in the number of Coliform and Faecalis Coliform has been noticed. Salmonella has been isolated also. But resource water proved to be sound. One of the supply pipes to the basins was broken and exposed , close to the highway The Study has also shown that ordinary refrigeration is ineffective for fish preservation .